The Polygonal Cell Shape and Surface Protein Layer of Anaerobic Methane-Oxidizing Methylomirabilislanthanidiphila Bacteria - Gambelli, Lavinia; Mesman, Rob; Versantvoort, Wouter; Diebolder, Christoph A.; Engel, Andreas; Evers, Wiel; Jetten, Mike S. M.; Pabst, Martin; Daum, Bertram; van Niftrik, Laura (Frontiers in Microbiology, 2021)
Methylomirabilis bacteria perform anaerobic methane oxidation coupled to nitrite reduction via an intra-aerobic pathway, producing carbon dioxide and dinitrogen gas. These diderm bacteria possess an unusual polygonal cell shape with sharp ridges that run along the cell body. Previously, a putative surface protein layer (S-layer) was observed as the outermost cell layer of these bacteria. We hypothesized that this S-layer is the determining factor for their polygonal cell shape. Therefore, we enriched the S-layer from M. lanthanidiphila cells and through LC-MS/MS identified a 31 kDa candidate S-layer protein, mela_00855, which had no homology to any other known protein. Antibodies were generated against a synthesized peptide derived from the mela_00855 protein sequence and used in immunogold localization to verify its identity and location. Both on thin sections of M. lanthanidiphila cells and in negative-stained enriched S-layer patches, the immunogold localization identified mela_00855 as the S-layer protein. Using electron cryo-tomography and sub-tomogram averaging of S-layer patches, we observed that the S-layer has a hexagonal symmetry. Cryo-tomography of whole cells showed that the S-layer and the outer membrane, but not the peptidoglycan layer and the cytoplasmic membrane, exhibited the polygonal shape. Moreover, the S-layer consisted of multiple rigid sheets that partially overlapped, most likely giving rise to the unique polygonal cell shape. These characteristics make the S-layer of M. lanthanidiphila a distinctive and intriguing case to study.